Management of Haemorrhagic Cystitis in dogs - Balakrishna, Vinay Hosakulu; Katoch, Ajay; Sharma, Ankur; Wadhwa, Des Raj; Kumar, Atul; R K, Asrani; Kumar, Adarsh; Bhawani, Ishani; Singh, Jagvir (Indian Journal of Veterinary Medicine, 2024)
Present study was carried out in the Department of Veterinary Medicine, Dr. G C Negi College of Veterinary and Animal Sciences, CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur, Himachal Pradesh, India. Detailed clinical evaluation of 6 dogs were carried out based on history and presenting clinical signs. The most common clinical sign noted were haematuria, dribbling of urine, pollakiuria and dysuria. Haematological examination, biochemical analysis, urine examination (urine dipstick, cytology and microbiological), and ultrasonographic studies were performed for the confirmatory diagnosis. Specific therapeutic of choice was advised based on cultural sensitivity test. E. Coli and Staphylococcus spp. were the bacteria isolated in the present study. Meropenem, Marbofloxacin and Nitrofurantoin were the most sensitive antibiotic found in the cultural sensitivity test. Complete amelioration of clinical signs was found in 4 dogs, 14 days post treatment whereas in 1 dog, treatment was extended till 21 days for complete recovery.